Fresno County Bar Association Old-Timers Luncheon - Watkins, Howard::::::::: (1984)
Fresno County's first County Counsel and longtime county historian Robert Wash sharing a story at the lectern; Donald Fischbach on far right The Fresno Hilton signs on the lectern